Characteristics of Hyloceregurt: Fermented Milk from Stems and Peel of Dragon Fruits: Karakteristik Hyloceregurt: Susu Fermentasi Dari Batang Tumbuhan dan Kulit Buah Naga - Sulistyarini, Indah; Palupi, Dwi Hadi Setya; Hesti, Ariani (Jurnal Farmasi Galenika (Galenika Journal of Pharmacy) (e-Journal), 2024)
Background: Fruitghurt, the result of fruit or fruit by-product fermentation, is a functional food. Functional foods are foods that are rich in benefits. A formulation of hyloceregurt has been derived from the stem and peel of the dragon fruit (Hylocereus polyrhizus), with potential as an immunomodulatory agent. Objectives: This study is aimed at determining the quality of hyloceregurt. Material and Methods: Hyloceregurt formula variations are made from fermented stem powder, fruit peel powder, or dragon fruit peel juice. The test include physical characteristics, chemical analysis, microbiology analysis, and hedonic test. Results: Hyloceregurt formula from the stems of the plant and the peel of the dragon fruit has almost the same physical characteristics that include a distinctive smell, an acidic taste with a pH ranging from 3-5, and a thick liquid consistency. The color of the hyloceregurt follows the waste of the dragon fruit used (pink and green). The chemical characteristics of hyloceregurt have met the SNI standard, including fat content with a range of 3.1-3.6% and protein content with a range of 4.95–6.74% b/b. The microbiological characteristics of hyloceregurt indicate that the value of the total plate figure is in the range of 1.1-3.3 x 109 CFU/mL. Panelists on the hedonic test preferred three formulas: 1% hyloceregurt from the peel powder or fresh peel fruit juice, and dragon fruit plant stems based on smell, taste, color, and consistency. Conclusions: All formulas in 1% fruit or by-fruit were the most preferred formulas, and based on the best physical characteristic tests and chemical content analysis, met the requirements of SNI 2981 of 2009. However, microbiologically, they still did not meet the requirements of SNI 2981 of 2009, so further tests still need to be carried out.